Revision of the Index of General Business Conditions - Crum, W. L. (The Review of Economics and Statistics, 1928)
R ECENTLY we have made two important changes in the Index of General Business Conditions. These include: a revision, involving a change of one of the constituents, in Curve B; and a revision, involving a modification of the secular trend and standard unit for each constituent, in Curve A.1 Both of these changes have been occasioned by the extraordinarily vigorous, remarkably sustained and widely prevalent public participation in stock speculation. The change in Curve B, which is discussed first below, comprises merely a refinement, in the bank debits data, intended to eliminate from the curve some of the confusing effects of the speculative outburst. The change in the Curve A is much more radical; and, since it may cause difference of opinion, we shall seek to explain in considerable detail the justification and implications of our substitution of the new results for those heretofore used.